2022
DOI: 10.1155/2022/7274115
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Transcranial Magnetic Stimulation (TMS) Paradigms as Treatment Options for Recovery of Language Deficits in Chronic Poststroke Aphasia

Abstract: Background. In an effort to boost aphasia recovery, modern rehabilitation, in addition to speech and language therapy (SALT), is increasingly incorporating noninvasive methods of brain stimulation. The present study is aimed at investigating the effectiveness of two paradigms of neuronavigated repetitive transcranial magnetic stimulation (rTMS): (i) 1 Hz rTMS and (ii) continuous theta burst stimulation (cTBS) each as a standalone treatment for chronic aphasia poststroke. Methods. A single subject experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 85 publications
(146 reference statements)
0
6
0
Order By: Relevance
“…Three studies 5658 with no more than five sessions of stimulation were removed. We also excluded three trials for data unextractable 5961 and one 62 without details about tDCS protocol, to which we contacted the corresponding authors without reply. The quantitative meta-analysis included 20 trials 13,24,3537,6377 with 840 participants (see Figure 1(a), Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies 5658 with no more than five sessions of stimulation were removed. We also excluded three trials for data unextractable 5961 and one 62 without details about tDCS protocol, to which we contacted the corresponding authors without reply. The quantitative meta-analysis included 20 trials 13,24,3537,6377 with 840 participants (see Figure 1(a), Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the sham rTMS group, one patient reported an increase in tiredness and one patient reported a mild headache. The rest of the five RCTs 61,70,71,75,76 reported no adverse effects. These articles did not observe severe side effect, such as seizes.…”
Section: Secondary Outcomesmentioning
confidence: 94%
“…Approximately 38% of adult stroke victims are subsequently diagnosed with aphasia ( 3 , 4 ), which further worsens the prognosis for these patients. The severity of aphasia is useful in predicting the functional autonomy of patients, as well as their short-term and long-term recovery outcomes following a stroke ( 5 , 6 ). Patients suffering from post-stroke aphasia (PSA) exhibit significantly elevated mortality rates and poorer functional outcomes compared to those without the condition ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…An important consideration is whether SLT should be paired with rTMS. Several studies suggested that when employed as a standalone therapy, rTMS holds promise in producing language improvements in PSA ( 6 , 18 20 ). On the contrary, the suggestion that rTMS could prime the brain for behavioral therapy, implying that it should be integrated with SLT, is met with challenges.…”
Section: Introductionmentioning
confidence: 99%
“…As a non-invasive, safe, and easily accepted treatment technique, transcranial magnetic stimulation (TMS) has a wide effect on neural networks in the brain by altering the excitability of neurons [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%